Nestin Expression in Spitzoid Lesions: An Immunohistochemical Characterization With Clinical and Dermoscopic Correlations. Issue 6 (July 2019) - Guanziroli, Elena; Del Gobbo, Alessandro; Coggi, Antonella; Venegoni, Luigia; Fanoni, Daniele; Ercoli, Giulia; Boggio, Francesca; Veraldi, Stefano; Cavicchini, Stefano; Berti, Emilio; Ferrero, Stefano; Gianotti, Raffaele
Abstract : Spindle or epithelioid melanocytic (Spitz) nevi usually affect children or adolescents and growth in the face or the lower extremities. Histologically, they may show cytoarchitectural atypia and mitotic figures that could represent diagnostic pitfalls with malignant melanoma. Atypical spitzoid tumors (AST) indicate lesions that microscopically show intermediate characteristics between benign nevi and malignant melanoma. Nestin expression has been evaluated in benign nevi and malignant melanoma, but no studies on its role in Spitz lesion have been elaborated so far. Our results indicate that Nestin could allow to discriminate between AST and malignant spiztoid melanoma; the typical dermoscopic pattern is also associated with benign nevi in contrast to the atypical pattern that accumunates AST and malignant spitzoid melanoma.